บทบาทรัฐสภาไทยในการตรากฎหมาย : ศึกษาบทบาทคณะราษฎรในกระบวนการนิติบัญญัติระหว่าง พ.ศ. 2475-2489 - นริศ มีสมบูรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
The objective of this research is to study the role of the Thai Parliament in lawmaking by focusing on the role of the People s Party in the legislative process from 1932 to 1946, the period since the revolution of the People s Party to the end of its power. The study shows that since the revolution brought about in 1932 by tile People s Party to changed tile regime of government from absolute monarch to monarchy under the law, tile Party had in every, possible fashion exercised its power to influence organs of the State it had established, namely the Parliament and the Council of Ministers. Its success had rendered it the most powerful political group of the time. Therefore, it is unsurprising that the substance and objectives of the laws passed during this period were [fundamentally] for the preservation and maintenance of the political power of the Party. On the other hand, a number of laws were enacted with an objective of eradicating its political rivals and those having different views out of the political realm. Finally, it had become the sole. political group which had true political might. Political agenda of the People s Party were not the only factors affecting the legislative process. The study also reveals that the politic economical and social contexts as well as the structure and composition of the Parliament and the bureaucracy all affected the substance and the procedural matter of the Parliament. In addition, it is found from the study that the pattern of the single Parliament all members of which were appointed according to the fir Constitution or that whose members derived equally from appointment and election allowed a group having political power, which was the People s Pato influence the legislative process. The single Parliament pattern was all an important reason of the confrontation between the Monarch and the Parli leading to the consequent abdication of King Prajadhipok in 1934.